Potencialna konfliktnost novih oblik ruralnosti v Sloveniji - Trček, Franc (IB revija (Ljubljana), 2012)
This paper examines new forms of living in rural areas; increasing numbers of the urban population now live there. The meeting of the old and new lifestyles in the rural area represents a potential source of conflict between new and old residents of the (semi)rural areas in the planning of future local and regional development. The purpose of this paper is to present new forms of rural living and to draw attention to existing and potential conflicts arising from them.
Keywords: Rural area; Ruralna področja; Urbanizacija; Urbanization; Regional development; Regionalni razvoj; Slovenia; Slovenija; prebivalci; sobivanje; konfliktnost